Redox Isomerization/(3+2) Allenoate Annulation by Auto‐Tandem Phosphine Catalysis. Issue 65 (13th October 2021) - Maddigan‐Wyatt, Jeremy T.; Blyth, Mitchell T.; Ametovski, Jhi; Coote, Michelle L.; Hooper, Joel F.; Lupton, David W.
Abstract: A phosphine‐catalyzed approach to pyrrolines has been developed that involves two mechanistically unlinked catalytic processes. The first involves the redox isomerization of amino crotonates to provide access to aliphatic tosyl imines, which then engage in a (3+2) annulation with various allenoates. The reaction shows generality, with 24 examples established, along with a low yielding and moderately enantioselective variant. Mechanistic studies indicate that the viability of the process is linked to the selection of catalysts with similar propensity to add to the two coupling partners. Abstract : Tandem catalysis allows a single catalyst to engage in two mechanistically distinct catalytic processes. While such approaches using transition metal catalysts are developed, they are less so in the field of organocatalysis. The use of a single phosphine catalyst is reported that mediates the redox isomerization of amino crotonates to give imines which then undergo (3+2) annulation with a range of allenoates in a second phosphine catalyzed process. Computational studies indicate that pivotal to the success of this reaction is the use of catalysts with similar ability to add to both allenoate and crotonate.